Romanians and Mount Athos: monasteries, archives, pilgrimages - Zahariuc, Petronel (Peter Lang, 2025)
"The relationships between the Romanian Principalities and the entire Orthodox area represented a fundamental framework of the Romanians' history, showing the Romanians' place and role in Europe's and the world's history. For five centuries (14th-19th), Moldavia and Walachia represented the main cultural and material backing for the Christian peoples in the Balkan Peninsula and the Near East. This volume includes 21 studies about or related to the relations of Romanians with Mount Athos: the general history of the Holy Mountain; the ties between certain monasteries of Mount and the Romanian Principalities; the Romanian sketes and the life of Romanian monks residing on Mount Athos; Mount Athos saints and personalities who had connections with the Romanian space; pilgrimages on Mount Athos in the 19th-20th centuries; the artistic relations between Mount Athos and the Romanian Principalities; the issue of Romanian monasteries submitted to Mount Athos"-- Provided by publisher